MANAGING POLICY NETWORKS: A SOCIAL MARKETING- AND COLLECTIVE INTELLIGENCE SYSTEMS-DRIVEN VIEW - Carmen Echebarria; Jose M. Barrutia (European Regional Science Association (ERSA), 2011)
This research contributes a new view of Policy Networks (PN) management. The research object is a successful PN practice in the Basque Country (BC) over an 8-year period, in relation to Local Agenda 21 (LA21) promotion. The Basque experience is studied using a qualitative and a quantitative approach. PNs are viewed as social marketing-driven collective intelligence systems built to have an effect on municipality commitment to LA21 (in terms of value, satisfaction and loyalty). The research concludes that by fostering the co-development `genome' (a mix of co-decision, co-creation, love, glory and money `genes') a commitment to the new tool is achieved.
Keywords: 330